2022
DOI: 10.52711/0974-360x.2022.00099
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of Pediococcus acidilactici on BALB/C mice Immunosuppressed by Cyclophosphamide

Abstract: Background: The live microorganisms that present in food in addition dietary supplements called Probiotics they have beneficial effect in the human intestine. In the last years, Probiotics has become within treatment options for several disease included immune system. The advent and use of probiotics seem to be increasing day by day all over the world. Objective: The current study included detection of efficacy Pediococcus acidilactici as immunomodulatory in mice that treated with cyclophosphamide. Design: To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…18 and Mohsin et al 19 showed that Weisella always appears in culture as white colonies, small, smooth and shiny. The presence of several fractions (contained proteins with a molecular mass less than 500 Da) may be the cause of T1 inhibition of studied bacteria; in vitro findings related to the peptidic nature of the LAB species linked to bacteria inhibition 20,21,22 , or may be occurrence the inhibition due to that some compounds work on the cell membrane and depolarize it, So, the cell wall synthesis inhibition, these compounds known as Diacetyl organic acids (lactic , formic, acetic and propionic) the pH of the medium was reduced as a result of this, So can compete for nutrients 20,23,24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 and Mohsin et al 19 showed that Weisella always appears in culture as white colonies, small, smooth and shiny. The presence of several fractions (contained proteins with a molecular mass less than 500 Da) may be the cause of T1 inhibition of studied bacteria; in vitro findings related to the peptidic nature of the LAB species linked to bacteria inhibition 20,21,22 , or may be occurrence the inhibition due to that some compounds work on the cell membrane and depolarize it, So, the cell wall synthesis inhibition, these compounds known as Diacetyl organic acids (lactic , formic, acetic and propionic) the pH of the medium was reduced as a result of this, So can compete for nutrients 20,23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies pointed out the antibacterial activity of LAB sp. because of hydroxyl fatty acids and phenolic compounds , these antimicrobial agents were conducted to act as decrease the electrochemical proton gradient, and H2O2 by peroxidation of lipids membrane ,so, changing the permeability of the cell membrane, resulting in disruption of the substrate transport mechanism [21][22][23] .…”
Section: Discussionmentioning
confidence: 99%